Step-by-step explanation:
There is no graph .so there is no way it can be answered.
please don't be offended
<span><span><span><span>2x</span>+y</span>+<span>−y</span></span>=<span>6+<span>−y</span></span></span><span><span>2x</span>=<span><span>−y</span>+6</span></span>Step 2: Divide both sides by 2.<span><span><span>2x</span>2</span>=<span><span><span>−y</span>+6</span>2</span></span><span>x=<span><span><span><span>−1</span>2</span>y</span>+3</span></span>Answer:<span> x=<span><span><span><span>−1</span>2</span>y</span>+3</span></span>
x-3=-2
x-3+3=-2+3
answer x=1
112 is that all multiplied and divided by three.
Answer:
5
Step-by-step explanation:
because by solving that the answer comes 5.70
Answer:
547
Step-by-step explanation:
Just subtract 813 - 266.
pls mark me as brainiest